Case study method key issues, key texts - Gomm, Roger.; Hammersley, Martyn.; Foster, Peter, 1951- (SAGE, 2000)
Case study is an increasingly popular approach in social research. This book is a comprehensive guide to the current uses and importance of case study methods.